EVALUASI PEMANFAATAN DANA BOS (BANTUAN OPERASIONAL SEKOLAH) TERHADAP OPTIMALISASI PROSES PEMBELAJARAN SISWA DI SMP N 4 MANDAU, DURI - Elvira Handayani; Almasdi Syahza; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract :Improving the quality ofhuman resourcesthat dependon the qualityof education, especiallyformal educationseenthroughthe learningprocess. But in fact, in an effortto meet the needsof educationthere are problemsintheeducationfundingproblem. Since 2007SMPN4 Mandau, Duriget helpBOS fundsareused foreducationfunding. However,notethattheBOSdoes notnecessarily make theprocess oflearningto be optimal. The purposeofthis study wastoevaluatethe use ofBOS fundstooptimize thelearning processof studentsinSMPN4Mandau, Duri. The method in this research is descriptive. With a total sample of 60 teachers. Data collection techniques used in this study were interviews, documentation and questionnaires.Meanwhile, to determine the effect of these two variables is using Chi Square analysis techniques. The results of this study stated that the BOS is beneficial to optimize the learning process of students in SMP N 4 Mandau, Duri.This is stated intheresultsin the category ofa highresponderas many as 54teachersandoftenas many as50teachers. From the analysis ofthe dataobtainedthe resultthat theChiSquareChiCalculate>ChiTableis12>3.481. Keywords: Utilization of Funds BOS, Learning Process Optimization